Variations in microbial community compositions and processes imposed under contrast geochemical contexts in Sicilian mud volcanoes, Italy - Chen, Jhen-Nien; Chiu, Yi-Ping; Tu, Tzu-Hsuan; Italiano, Francesco; Wang, Pei-Ling; Lin, Li-Hung (Frontiers in Microbiology, 2024)
Terrestrial mud volcanoes represent surface features of channels for subsurface methane transport and, therefore, constitute an important source of methane emission from natural environments. How microbial processes regulate methane emissions in terrestrial mud volcanoes has yet to be fully addressed. This study demonstrated the geochemical characteristics and microbial communities of four mud volcano and seep sites in two geological settings of Sicily, Italy. At sites within the accretionary wedge that exhibited higher methane and sulfate concentrations, the communities were dominated by members capable of catalyzing methane and sulfate metabolisms and organic degradation. In particular, both anaerobic and aerobic methanotrophs were abundant and their abundance distribution coincided with the geochemical transition. In contrast, the sites near Mount Etna were characterized by high fluid salinity, CO2, and low methane and sulfate concentrations, with communities consisting of halophilic organic degraders and sulfur metabolizers, along with a minor presence of aerobic methanotrophs. Substantial variations in community composition and geochemistry across spatial and vertical redox gradients suggest that physicochemical contexts imposed by the geology, fluid path, and source characteristics play a vital role in shaping community composition and cycling of methane, sulfur and organic carbon in Sicily mud volcanoes.